The Impact of Behavioral Biases on Investment Decisions among Nepalese Investors (Dristikon: A Multidisciplinary Journal, 2025)
This study examines the impact of behavioral biases on investment decisions among Nepalese investors. Despite growing stock market participation, there is limited research on the investment characteristics and biases predominant in Nepal. The study aims to assess these characteristics, analyze behavioral biases, and evaluate their influence on investment decisions. This study was used a descriptive and causal research design to analyze the impact of behavioral biases on investment decisions. The total population of the study was unknown. Therefore, a sample size of 120 individual investors was chosen using the convenience sampling techniques from retail investors through questionnaires. The questionnaires were collected both online and offline. The study was analyzed using descriptive statistics and inferential statistics to evaluate the data. The   study discloses a balanced gender and highly educated respondents. The results of this study are significantly positive relationship between behavioral biases and investment decisions. The study on Nepalese investors discloses a mature, knowledgeable population with diverse investment strategies influenced by behavioral biases. The implication of the study’s that increasing awareness of behavioral biases can enhance investment decision and more effective financial education and advisory practices. Future research could be focused with mediating and moderating variables measures relationships behavioral biases and investment decision making.